An antigen-specific semi-therapeutic treatment with local delivery of tolerogenic factors through a dual-sized microparticle system blocks experimental autoimmune encephalomyelitis. (October 2017) - Cho, Jonathan J.; Stewart, Joshua M.; Drashansky, Theodore T.; Brusko, Maigan A.; Zuniga, Ashley N.; Lorentsen, Kyle J.; Keselowsky, Benjamin G.; Avram, Dorina
Abstract: Antigen-specific treatments are highly desirable for autoimmune diseases in contrast to treatments which induce systemic immunosuppression. A novel antigen-specific therapy has been developed which, when administered semi-therapeutically, is highly efficacious in the treatment of the mouse model for multiple sclerosis, experimental autoimmune encephalomyelitis (EAE). The treatment uses dual-sized, polymeric microparticles (dMPs) loaded with specific antigen and tolerizing factors for intra- and extra-cellular delivery, designed to recruit and modulate dendritic cells toward a tolerogenic phenotype without systemic release. This approach demonstrated robust efficacy and provided complete protection against disease. Therapeutic efficacy required encapsulation of the factors in controlled-release microparticles and was antigen-specific. Disease blocking was associated with a reduction of infiltrating CD4 + T cells, inflammatory cytokine-producing pathogenic CD4 + T cells, and activated macrophages and microglia in the central nervous system. Furthermore, CD4 + T cells isolated from dMP-treated mice were anergic in response to disease-specific, antigen-loaded splenocytes. Additionally, the frequency of CD86 hi MHCII hi dendritic cells in draining lymph nodes of EAE mice treated with Ag-specific dMPs was reduced. Our findings highlight the efficacy of microparticle-based drug delivery platform to mediate antigen-specific tolerance, and suggest that such a multi-factor combinatorial approach can act to block autoimmunity.